Primary echinococcal cyst in the thyroid gland: a case report from Iran - Mehrdad Moghimi; Seyed Kamran Kamrava; Ashkan Heshmatzade Behzadi; Ali Mohammad Asghari; Maryam Jalessi; Mona Masoumeh Naraghi; Elnaz Ehteshamia Afshar (Journal of Infection in Developing Countries)
Hydatid disease is prevalent in most sheep-raising countries in Asia , Australia , East, and Southern Europe. Hydatid disease caused by Echinococcus granulosus is often manifested by a slow growing cyst mass. Hydatid cysts may be found in almost every parts of the body. However the lungs and liver are the most involved locations. Due to the vital cycle of the parasite the thyroid gland is an uncommon site of infection even in the countries where the disease is endemic. However, hydatic origin was suspected in only 50% of patients preoperatively and immunologic test had 33% false positive rate. Although hydatid cyst was considered intra-operatively and confirmed by a frozen section histology. This study is to report a case of primary hydatid disease of the thyroid.